Con desarrollo:
1) 3x+(5-2x)+4=6
2) 4x-(5-7x)-6=11
3)-3x+2-(x+3)=-5x+4
4) 4+5x-(3-3x)=6x-7
5)8-5x+3(2+x=-(x+6)
6)9-3x+2(3-x)=-5(x+4)-x
7))5-(3y-6y-8)-7y=2y+16-9
8)3(y-4)=(3y-5-4y)-(2-5y+10)
Respuestas
Respuesta dada por:
19
preferí hacerlo en cuaderno, espero te sirva.
Adjuntos:
![](https://es-static.z-dn.net/files/dcd/e1cc10e57bb45d6cba70888e2b27c09d.jpg)
neyrali:
gracias amiga . puedes hacerme
Preguntas similares
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años